1999
DOI: 10.1146/annurev.astro.37.1.363
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy Processes in Young Stellar Objects

Abstract: ▪ Abstract  Observational studies of low-mass stars during their early stages of evolution, from protostars through the zero-age main sequence, show highly elevated levels of magnetic activity. This activity includes strong fields covering much of the stellar surface and powerful magnetic reconnection flares seen in the X-ray and radio bands. The flaring may occur in the stellar magnetosphere, at the star-disk interface, or above the circumstellar disk. Ionization from the resulting high-energy radiation may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
671
1
16

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 698 publications
(727 citation statements)
references
References 210 publications
39
671
1
16
Order By: Relevance
“…Angular momentum conservation during the initial contraction of a proto-stellar cloud eventually leads to a central pre-main sequence star surrounded by a disk. As angular momentum is transported outward through the disk, material must move from the disk, either onto the star or into a wind (see, e.g., Feigelson & Montmerle 1999). Theoretical studies on star formation suggest that a substantial portion of a star's final mass is accreted through such a disk.…”
Section: Discussionmentioning
confidence: 99%
“…Angular momentum conservation during the initial contraction of a proto-stellar cloud eventually leads to a central pre-main sequence star surrounded by a disk. As angular momentum is transported outward through the disk, material must move from the disk, either onto the star or into a wind (see, e.g., Feigelson & Montmerle 1999). Theoretical studies on star formation suggest that a substantial portion of a star's final mass is accreted through such a disk.…”
Section: Discussionmentioning
confidence: 99%
“…We then consider a separate X-ray illuminated model in which the gas is solely exposed to X-rays, but not FUV photons, aiming at evaluating the influence of these two energy sources on the chemistry. There is evidence for X-ray emission in protoplanetary disks (Feigelson & Montmerle 1999). The main effect of X-rays on the chemistry is the ionization of the gas producing high-energy photoelectrons (ph-e − ), which further ionize and dissociate the species.…”
Section: Chemical Modelmentioning
confidence: 99%
“…Using such proxy it has been shown that magnetic activity increases with rotation rate and that above a given rotation rate (that depends on the stellar spectral type but is around Ros ∼ 0.1), stellar magnetic activity first saturates (Pizzolato et al 2003;Wright et al 2011) and then possibly "over-saturates" for extremely fast rotation rate such as the ones found in young solar-like T-Tauri stars (Feigelson and Montmerle 1999). One can thus simply seek to characterize how the saturation of the dynamo generated field can be linked to the saturation of solar-like star X-ray emissivity.…”
Section: Nonlinear Dynamo Effect Magnetic Activity and Cyclesmentioning
confidence: 99%